Solubilization and enhanced degradation of benzene phenolic derivatives—Bisphenol A/Triclosan using a biosurfactant producing white rot fungus Hypocrea lixii S5 with plant growth promoting traits - Chaturvedi, Mridula; Kaur, Navpreet; Rahman, Pattanathu K. S. M.; Sharma, Shashi (Frontiers in Microbiology, 2024)
Endocrine disrupting chemicals (EDCs) as benzene phenolic derivatives partition to organic matter in sludge / soil sediments being hydrophobic and show poor bioavailability to microbes. For degradation, solubilization of these hydrophobic pollutants is desirable for enhanced mass transfer to microbial cells. In the present study, we have reported for the first time, the degrading potential of a versatile white rot fungal isolate S5 identified as Hypocrea lixii with simultaneous production of lipopeptide biosurfactant (BS) during degradation of Bisphenol A (BPA)/Triclosan (TCS) under shake flask conditions. Sufficient growth of WRF for five days before supplementation of 50 ppm EDC (BPA / TCS) in set B, showed an increase in degradation rates by 23% and 29% with corresponding increase in secretion of lignin modifying enzymes compared to set A wherein almost 84 % and 97% inhibition in fungal growth was observed when BPA /TCS were added at time of fungal inoculation. Further in set B, EDC concentration stimulated expression of laccase and Lip with 24.44 U/L of laccase and 281.69 U/L of lignin peroxidases (Lip) in 100 ppm BPA and 344 U/L Lip in 50 ppm TCS supplemented medium compared to their respective controls (without EDC). Biodegradation was also found to be correlated with lowering of surface tension from 57.02 mN/m (uninoculated control) to 44.16 mN/m in case of BPA and 38.49 mN/m in TCS, indicative of biosurfactant (BS) production. FTIR, GCMS and LC-ESI/MSMS confirmed the presence of surfactin lipopeptide isoforms. The WRF also displayed positive plant growth promoting traits as production of Ammonia, Indole acetic acid, Siderophores, Zn solubilization and 1-1-aminocyclopropane-1-carboxylate (ACC) deaminase activity, reflecting its soil restoration ability.